The Effect of Implementing an Integrity Zone on Employee Performance with Work Culture as a Moderating Variable - Yanti Rahmayanti; Herwan Abdul Muhyi; Iwan Sukoco (Business and Applied Management Journal, 2026)
The implementation of bureaucratic reform in higher education institutions requires governance systems that emphasize transparency, accountability, integrity, and service excellence. This study aims to examine the effect of Integrity Zone implementation on employee performance in student services at the Directorate of Academic and Student Affairs. A quantitative research design was employed using a survey method involving 70 students who had directly utilized student services. Data were collected through a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and path analysis. The descriptive findings indicate that the implementation of the Integrity Zone was perceived at a high level, with an overall mean score of 4.04, while employee performance was also rated highly, with a mean score of 3.99. Among the Integrity Zone dimensions, Public Service Quality Improvement achieved the highest score (4.11), whereas Productivity emerged as the strongest dimension of employee performance (4.04). The inferential analysis revealed that the implementation of the Integrity Zone had a positive and significant effect on employee performance in student services. The findings offer practical implications for university administrators seeking to strengthen governance quality and enhance student-centered service delivery.